Determination of Temperature Coefficients of Materials in RF BAW Resonators - Tag, Andreas; Bader, Bernhard; Pitschi, Maximilian; Wagner, Karl Christian; Weigel, Robert; Hagelauer, Amelie Marietta (German Microwave Conference, 2015)
A new, accurate, and fast approach for determining the temperature coefficients of the thin film materials used in RF BAW components has been developed allowing the precise modeling of BAW components at different ambient temperatures. The presented method is based on the investigation of several resonance frequencies of the resonators with different layer-stacks. The problem of determining the temperature coefficients from broadband resonator simulations and measurements was formulated as an overdetermined linear system of equations and solved by using the weighted least square method. The presented approach has been verified by measurements.
elib2cris::1512001600,tag2015